Classification of chest radiographs for epidemiological purposes by people not experienced in the radiology of pneumoconiosis. Issue 3 (August 1981) - Copland, L; Burns, J; Jacobsen, M
Abstract : Under controlled conditions 16 people (eight non-medical) inexperienced in the radiology of occupational lung diseases repeatedly classified 300 selected chest radiographs using the 1971 ILO U/C International Classification of Radiographs of Pneumoconioses. Eight experienced medical readers had previously classified 220 of the selected radiographs for profusion of small rounded opacities. Variability among readers was greater in experimental panels than among the experienced readers. But the average consistency between pairs of novice readers in their use of the 12 categories of profusion for the same radiographs was similar (about 29%) to the average consistency among the experienced readers. Subsequent work with nine of the participants showed that eight of them were able to produce classifications of coal miners' chest radiographs that correlated well with estimates the miners' exposures to respirable coal mine dust. It is concluded that the ILO classification scheme provides a sound descriptive system for recording the appearances of chest radiographs. Under controlled conditions the scheme may be used for epidemiological studies by those with no specialist knowledge or clinical experience. This presupposes that the radiographs concerned will have been examined previously for diagnostic purposes by a suitable qualified physician.